Physical and organoleptic characteristics of pre- rigor leg-twisted red Sokoto goat carcasses (2012)
The efficiency of leg-twisting treatment as a method of improving goat muscle tenderness and eating qualities were determined. Twelve matured good grade Red Sokoto does were dressed conventionally with the hind hoofs retained on a randomly selected side of each carcass; Leg twisting was effected by inserting one hoof into a slit made anterior to the flank muscle. Both sides were suspended by the Achilles tendon and moved into the cold room within 30 min post-mortem and chilled for 48 hours. The semimembranosus (SM), the semitendinosus (ST) and the biceps femoris (BF) were excised from each half and used for the study. The result of the study showed that the sarcomere increased in all the three muscles as a result of leg-twisting. The treatment also improved tenderness by 1.4, 6.17 and 32.71 percent for SM, ST and BF muscles respectively. Except in the SM, where the water holding capacity (WHC) increased (P>0.05) there was a reduction in the WHC of the other two muscles while the drip loss increased as a result of leg-twisting in the three muscles. The sensory score for SM improved significantly (P<0.05) in all the parameter measured while the improvement in other muscles were not significant (P>0.05).